Effect of plant hormone concentration on kinsenoside production in anoectochilus formosanus plantlets - Mohd Misbah, Maryam Sakinah (2016)
Orchids are recognized as the rich sources of natural compound, particularly for medicinal uses. One of the orchid species well-known for medicinal uses is Anoectochilus formosanus. This orchid species is largely distributed in Taiwan and can be found in all regions around the world excluding Antarctica and hot deserts. A research finding justifies kinsenoside as the major compound responsible for its pharmacologic properties (Hsieh et al., 2011). It is also being called "King of Medicine" because of its diverse pharmacologic effects such as cancer prevention, liver protection and diabetes and for prevention of cardiovascular disease (Hossain, 2011 ). However, this species is at the risk of extinction due to the high demand of their pharmacologic compound and low propagation rate (Ket et al., 2004 ). Hence, this research aims to observe the differences of kinsenoside production by in vitro A. formosanus plants at different concentrations of a plant growth regulator (6-Benzylamino purine/BAP) to determine the accurate concentration to maximize the valuable compound production and sustain their population. BAP hormone regulator was used because of its ability as an abiotic elicitor to stimulate morphological changes in a psychological or developmental processes. Using tissue culture techniques, Anoectochilus plantlets were grown on media supplemented with various concentration of BAP (0, 1.0, 2.0 and 4.0 mg/mL) in replicates for each concentration and harvested on day 0, 14 and 28. Based on this research, it was found that media supplemented with 4.0 mg/mL BAP was the most favourable by the in vitro Anoectochilus formosanus plantlets to produce more kinsenoside over time. While none of the BAP concentrations leads to the changes of morphology and growth of the plantlets since there was no shoot production and plantlet length increment throughout the short duration of studies (28 days).